2018
DOI: 10.1128/iai.00014-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Novel Protective Antigens for the Development of a Candidate Tuberculosis Subunit Vaccine

Abstract: The development of a vaccine against tuberculosis (TB), a disease caused by Mycobacterium tuberculosis, is urgently needed. The only currently available vaccine, M. bovis BCG, has variable efficacy. One approach in the global vaccine development effort is focused on boosting BCG using subunit vaccines. The identification of novel antigens for inclusion in subunit vaccines is a critical step in the TB vaccine development pathway. We selected four novel mycobacterial antigens recognized during the course of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 59 publications
6
49
1
Order By: Relevance
“…Moreover, the di erences in animal models and immunization routes will a ect the protective response induced by vaccines. Stylianou et al [46] reported that when BALB/c and C57BL/6 mice were primed with BCG and boosted 10 weeks later with ChAdOx1.PPE15 vaccine, followed by challenge with aerosolized M. tuberculosis, the booster ChAdOx1.PPE15 only improved the protection provided by BCG in C57BL/6 mice and not in BALB/c mice. A recent study compared the e ects of di erent immunization routes [intranasal (i.n.…”
Section: Micementioning
confidence: 99%
“…Moreover, the di erences in animal models and immunization routes will a ect the protective response induced by vaccines. Stylianou et al [46] reported that when BALB/c and C57BL/6 mice were primed with BCG and boosted 10 weeks later with ChAdOx1.PPE15 vaccine, followed by challenge with aerosolized M. tuberculosis, the booster ChAdOx1.PPE15 only improved the protection provided by BCG in C57BL/6 mice and not in BALB/c mice. A recent study compared the e ects of di erent immunization routes [intranasal (i.n.…”
Section: Micementioning
confidence: 99%
“…However, due to the high seroprevalence of the most popular human adenoviruses in the population [21,22], other primate adenoviruses with lower human seroprevalence like gorilla and chimpanzee ones have been pursued [6,23,24]. These primate adenoviruses have been shown here and by others to be effective vector platforms [9][10][11][12]23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A novel vaccine vector was recently derived from the chimpanzee adenovirus isolate Y25 subgroup E. This viral vector known as ChAdOx1 was engineered at the University of Oxford as a replication-incompetent virus by deletion of its E1 region [8]. Recombinant ChAdOx1 vectors have successfully been used in vaccines against a wide variety of pathogens [9][10][11][12][13]. Furthermore, phase I clinical trials with ChAdOx viral vectors against diseases such as influenza (NCT01818362, NCT01623518), tuberculosis (NCT01829490, NCT03681860), MERS (NCT03399578), HIV (NCT03204617), malaria (NCT03203421), and meningitidis B (ISRCTN46336916) have demonstrated their safety and immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination-induced T-cell populations expressing certain surface molecules i.e. CXCR3, CCR7, CD45RA signify specific subsets which can predict desirable clinical responses (Mpande et al, 2018;Stylianou et al, 2018). Nextgeneration sequencing has revealed differential V-J recombination patterns (at the gene level) among T-cell receptor gamma-delta (TCR-gd) Vg9Vd2 cells in patients with pulmonary TB (Cheng et al, 2018).…”
Section: Recent Data On Cellular Immune Responses and Applicability Tmentioning
confidence: 99%